Analysis of guest satisfaction through the service quality of the Aloha department at Aloft Bali Seminyak - Gede Aditya Gunawan; Budi Susanto; I Nyoman Meirejeki; Ida Ayu Ketut Sumawidari (Journal of Applied Sciences in Travel and Hospitality, 2022)
This research discusses the assessment of guest satisfaction through the service quality that is provided by the Aloha department at Aloft Bali Seminyak. This research aim is to identify if the guest expectations match with the guest experience (perception) regarding the service quality provided by the Aloha department at Aloft Bali Seminyak and to analyze the indicators needed to be maintained and improve to enhance the service quality of the Aloha department. The data used in this research are quantitative. The method of data collection was observation and questionnaire. The total of respondents used in this research is 80 respondents with the incidental sampling method. Data analysis techniques applied in this research are Service Quality (ServQual) and Importance-Performance Analysis which use Cartesian diagrams. The result of the research indicates 4 indicators resulting negative gap, 11 indicators resulting positive gap, and 1 indicator with zero gaps between guest perception and expectation. The importance-Performance analysis found 3 indicators on Quadrant A which the major weakness need improvement, those indicators are cleanliness of the lobby area, the ability of the Aloha talent to provide fast and precheck-ink & check out services, and recognition of the guest name by the Aloha talent. However, there are 4 indicators found on Quadrant B as a major strength of services and they need to be maintained to make guest satisfaction.